2017
DOI: 10.1111/1467-8551.12219
|View full text |Cite
|
Sign up to set email alerts
|

From Politically Naïve to Politically Mature: Conceptualizing Leaders’ Political Maturation Journey

Abstract: This paper contributes to the literature on organizational politics and leadership. Current studies of leaders’ engagement in politics neglect notions of learning and development. The current paper aims to overcome this shortcoming by providing a developmental perspective on leaders’ engagement in organizational politics. Using in‐depth qualitative interviews with leaders at different seniority levels, the study examines developmental patterns in leaders’ willingness and ability to engage in organizational pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 78 publications
(146 reference statements)
2
34
1
3
Order By: Relevance
“…Our findings (Aggregate Theoretical Dimension 2) extend this work by demonstrating how such attitudes could be shaped by developmental feedback that encourages male and female leaders to navigate organizational politics differently (proactively vs defensively). Yet, the importance of political skill in leadership roles is widely documented (Ammeter, Douglas, Gardner, Hochwarter & Ferris, 2002;Buchanan, 2016) and a more proactive approach to politics sets apart mid-level leaders from senior ones (Doldor, 2017). In sum, we demonstrate that developmental feedback is less likely to direct women towards nurturing visionary and political skills required for senior leadership roles (Day & Dragoni, 2015).…”
Section: Gender Bias and Feedback Researchmentioning
confidence: 68%
“…Our findings (Aggregate Theoretical Dimension 2) extend this work by demonstrating how such attitudes could be shaped by developmental feedback that encourages male and female leaders to navigate organizational politics differently (proactively vs defensively). Yet, the importance of political skill in leadership roles is widely documented (Ammeter, Douglas, Gardner, Hochwarter & Ferris, 2002;Buchanan, 2016) and a more proactive approach to politics sets apart mid-level leaders from senior ones (Doldor, 2017). In sum, we demonstrate that developmental feedback is less likely to direct women towards nurturing visionary and political skills required for senior leadership roles (Day & Dragoni, 2015).…”
Section: Gender Bias and Feedback Researchmentioning
confidence: 68%
“…In this political arena they are likely to demonstrate different motivations for political behavior which may reveal a constructive but also a destructive aspect (Ellen et al , 2013). Similarly, Doldor (2017) has suggested that political leadership relies on political tactics ranging from the pro-social (coalitions, friendliness, networking, self-promotion) to anti-social (attacking, blaming or exploiting others, coercion, blackmail). With this in mind, we now introduce leaders’ political behaviors.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, currently, there is little insight into what drives leaders to engage in organizational politics (Doldor et al, 2013). Until now, studies have mostly investigated what politics "does" in organizations, its implications and consequences (Lepisto and Pratt, 2012), rather than exploring the motivations for such action (Doldor, 2017;Doldor et al, 2013;Kapoutsis, 2016). This paper aims to address this research gap by exploring leaders' drives for political behavior, thereby investigating organizational politics at a micro-level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations